The Use of Types of Tenses in The Subtitles of Muniba Mazari Speech - Uni, Ni Kadek; sulatra, I komang; Putra, I G B Wahyu Nugraha (Journal of Language and Applied Linguistics, 2023)
The study aimed to find out the types of English tenses found in “We All Are Perfectly Imperfect” speech. The descriptive qualitative method was applied in analyzing the data. For collecting the data, this study used observation and documentation method. This study applied Cowan’s theory (2008) to find out the types of English tenses. Those are three types of tenses: past, present, and future tenses in which each having four tense aspects with twelve tense aspects in total. The result of this research study shows that there are seven types of tense aspects come from those three main tenses present, past and future tenses that were found in this speech. In present tense there were simple present, present continuous, present perfect and present perfect continuous tense with total 115 data (48,0%). In past tense there were simple past, and past continuous tense with the total 111 data (46,0%). Then in future tense there was type of simple future tense with 14 data (5,8%). The finding shows that the most dominant type of the tenses found in the speech “We All Are Perfectly Imperfect” is the type of present tense because the speaker in the speech mostly talking about something in the present moment and then the lower number of the data found is the type of future tense with percentage because the speaker was rarely talking about something that is prediction to happen in the future time.